The Organization Man Still Matters: Sinclair Lewis’s Babbitt - Hartwig, Marcel (Current Objectives of Postgraduate American Studies, 2012)
Ever since its publication Sinclair Lewis’s Babbitt “(1922) has been a thorn in the side of many businessmen and organizations. Debates ranging from its literary merit to its content caused a stir during the ‘Roaring Twenties.’ However, the novel could also be read as a starting point in a series of writings about the evolution of modern business and businessmen. The paper argues that Babbitt traces developments of the contemporary organization man and his estrangement from his personal culture due to a boosting consumer culture. Lewis’s Babbitt “thus is an early predecessor of sociologist William H. Whyte’s organization man and of the yuppie of the 1980s.